AGGRESSION AND STRESS LEVEL IN RECOVERED DRUG ADDICTS - Kaur, Jasmine; Sona (International Journal of Psychosocial Rehabilitation, 2021)
Aggression is described as an action or behavior that is meant to hurt or inflict distress. It is usually a reaction to something unpleasant. Stress is a form of mental pressure. It can lead to many serious health issues if experienced in high amounts. This research was conducted to study theaggression level and stress levelin recovered drug addicts. A total number of 30 samples were selected. All were recovered drug addicts.Perceived stress scale (PSS-10) by Sheldon Cohen and Buss-Perry Aggression scale were used. The results indicated that recovered drug addicts’ experience extraordinarily high levels of aggression and stress.